Peer-Group support based on the chronic care model for improving HIV patients' caring ability - Nursalam Nursalam; Tintin Sukartini; Misutarno Misutarno; Diah Priyantini; Silvia Farhanidiah; Kondwani Joseph Banda; Sirikanok Klankhajhon; Hidayat Arifin (Faculty of Nursing Universitas Padjadjaran, 2024)
Background: The ability of caring of HIV patients toward a condition is still relatively low, especially during a pandemic, which makes the patient's immune condition more susceptible to decline. This study aims to develop peer-group support based on a chronic care model (CCM) to improve the ability of HIV patients in caring during the COVID-19 pandemic. Methods: An explanatory study with cross-sectional was conducted. A total of 375 respondents were recruited with convenience sampling. The exposure were individual characteristic factors, health system factors, support system factors, environmental factors and peer group support based on chronic care model. Meanwhile the outcome was improvement of patient’s ability in caring. Statistical analyses were conducted using SPSS version 21 and SEM-PLS.